2018
DOI: 10.18535/ijsrm/v6i1.mp03
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Short Term Aerobic Exercise (Football Training) On Lipid Profile And Myoglobin Levels In Apparently Healthy Students Of College Of Health Sciences, Nnamdi Azikiwe University, Nnewi Campus, Anambra State, Nigeria

Abstract: This study investigated the effect of short term aerobic exercise on lipid profile and myoglobin levels in apparently healthy students of College of Health Sciences, Nnamdi Azikiwe University, Nnewi Campus, Anambra State, Nigeria. A total of 60 apparently healthy young students aged between 18-40 years were randomly selected for the study. They were rested for a period of two weeks after which they were subjected to football exercise for 30 minutes (3 times) in a week for a period of 3 weeks. The demographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Many studies have examined the effect of PA on biochemical parameters (Priscilla et al, 2018) and body composition (Lee, Libman, et al, 2020). The present study reported that aerobic PA caused a significant decrease in TG levels probably via increasing lipoprotein lipase (LPL) activity in skeletal muscle due to a reduction in the adenosine triphosphate: adenosine monophosphate (AMP) ratio resulting in upregulation of AMP‐activated protein kinase and subsequently LPL activity (Plaisance et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the effect of PA on biochemical parameters (Priscilla et al, 2018) and body composition (Lee, Libman, et al, 2020). The present study reported that aerobic PA caused a significant decrease in TG levels probably via increasing lipoprotein lipase (LPL) activity in skeletal muscle due to a reduction in the adenosine triphosphate: adenosine monophosphate (AMP) ratio resulting in upregulation of AMP‐activated protein kinase and subsequently LPL activity (Plaisance et al, 2009).…”
Section: Discussionmentioning
confidence: 99%